Making translational value: identifying ‘good targets’ for clinical research on gene editing and induced pluripotent stem cell technologies - Morrison, M; Bartlett, A (Elsevier, 2022)
Biomedical translational researchers aim to develop knowledge and techniques arising from research in the life sciences into clinical applications. Using the examples of induced pluripotent stem cells (iPSC) and gene editing, this paper examines how translational researchers identify and justify which particular conditions or patient populations make ‘good targets’ for translational research with particular technologies. Drawing on empirical data from qualitative interviews with academic and commercial researchers working on clinical translation of iPSC and gene editing in the UK, this study illustrates how particular combinations of technology and disease (for example iPSC-derived cells as a therapy for Parkinson's disease or gene editing for Cystic Fibrosis) were evaluated and justified as worth pursuing. The results show that translational researchers anticipate the ways in which their therapies-in-the making will be evaluated by other groups including regulators, physicians, patients, and bodies charged with health technology assessment. Each of these groups have their own understandings of what is valuable in a novel health technology and their own criteria for evaluation. As a result, translational researchers must supplement justifications that draw on scientific and industrial logics, with accounts that recognise other forms of worth, including market and civic registers of justification. These findings give an insight into the factors shaping contemporary biomedical translational research. The current regulatory and health technology adoption frameworks exert a strong influence, with elements such as ‘safety’ or ‘unmet need’ being common to most justification. However there was also sufficient flexibility to allow different competing definitions of what safety or unmet need might look like.